Desain Teknis Bangunan Bronjong pada Ruas Jalan Ilngei - Aruidas Kabupaten Kepulauan Tanimbar - Hattu, Stela Velly; Hamkah, Hamkah; Hukom, Edison (JURNAL ILMIAH NUSANTARA, 2025)
The Ilngei Aruidas road section, Tanimbar Islands Regenchy, is one of the Collector Road sections located in Tanimbar Islands Regenchy using flexible pavement with a length of 59 KM, a pavement width of 5.5 meters. Based on geographical lacation, the route og the Ilngei Aruidas road is mostly on hills and slopes which tend to be influenced by weather conditions which result in landslides on the Ilngei Aruidas road, especially at the Sta 39+970 with a total length of the landslide reaching 30 meters with a landslide height reaching 4.0.The aim of this research is to determine the type of gabion the is suitable for dealing with landslides on the Ilngei Aruidas road, Tanimbar Islands Regency, road, Tanimbar Islands Regechy, as well as planning safe gabion dimensions on the Ilngei Aruidas road, Tanimbar Islands Regechy. The results of the planning analysis show that the appropriate type of gabion to use is the wire gabion type with the following gabion dimension, 4 meters high, 3 meters wide and 30 meters long, stability against slinding 262,9 > 1.5 stability against overturning 1,46>1,5 and stability to bearing capacity-omax-843,2 kN/m2 qa-15,40 kN/m2.